PENGARUH METODE DISCOVERY LEARNING TERHADAP KEMAMPUAN BERFIKIR KRITIS SISWA DENGAN VARIABEL MODERATOR MOTIVASI BELAJAR SISWA - Novi Satria Pradja; Irma Irma Nurmilati (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2019)
Abstract: The weakness of critical thinking ability effect to  deficient learning result. The ability of critical thinking is effected by discovery learning method with the moderator of student learning motivation variable. The aim of the research is to know the effect of discovery learning method to critical thinking ability with the moderator of student learning motivation variable. The method is caution experiment  by using factorial  design research 3x2. The subject of the research are students of SMK Negeri 1 Kadipaten, those are XI OTKP 4 class as experiment class and XI OTKP 3 as control class. After having precondition test using by normality test and homogeneity on pretest and posttest can be concluded such as : 1) There it is have deference of critical thinking ability between the class uses discovery learning method and the class using  Talk method, 2).There it is have difference of critical thinking ability  between student has high, medium, and low  learning motivation. 3) The learning method has interaction with the learning motivation in effecting student critical thinking ability.Kata kunci: Discovery Learning Method, Learning Motivation, Critical Thinking Ability